DAYA TARIK KONTEN MEDIA SOSIAL TIKTOK TERHADAP WISATA SPIRITUAL PENGELUKATAN (STUDI KASUS AKUN TIKTOK TAMAN BEJI GRIYA WATERFALL 369) - Made Ika Kusuma Dewi; I Nyoman Surpa Adisastra; Bagus Ade Tegar Prabawa (UHN IGB Sugriwa Denpasar, 2025)
The attraction of tiktok social media content towards spiritual tourism plays a significant role in promotional media. tiktok content is often used as a link in information and connection between creators and the public. The public obtains information about spiritual tourism, namely hugging on the tiktok social media account @beji_griya_waterfall and creators can make a positive contribution in increasing local community income due to the management of spiritual hugging tourism at Beji Griya Waterfall Park and tourists who get spiritual healing and healing experiences. In the digital era, technological developments and the presence of social media have changed the way individuals interact, communicate and share information. How social media such as tiktok provides activities in communicating through video content and the features provided by tiktok social media can be an effective tool in conveying information about the spiritual tourism experience of melukat and healing at Beji Griya Waterfall Park. This approach aims to find out how TikTok social media has an impact on the audience at Beji Griya Waterfall Park. The type of approach used in this research is a qualitative perspective. Data analysis in this research was carried out using the triangulation technique analysis method, defined as a way of validating the data. This data includes using observation, interview and documentation techniques. Keywords: Social Media, Tiktok Account @beji_griya_waterfall, Spiritual Tourism, Taman Beji Griya Waterfall